Hypothermia Associated With Melatonin Ingestion in a Child With Autism. Issue 5 (September 2019) - Erden, Semih
Abstract : Abstract: Autism spectrum disorder is a neurodevelopmental disorder characterized by social interaction and communication disorder and restrictive and repetitive behaviors. Sleep disorders are frequently observed in children with autism spectrum disorder. We present a case of hypothermia in an autistic child with a sleep disorder whose body temperature decreased to 34°C after a single dose of melatonin. Hypothermia continued for 2 more days, but her nighttime sleeping problems decreased. This case is important because it demonstrates the possible risk of hypothermia with melatonin use in children with autism with a sleep disorder.